Novel National High-Precision Time Synchronization System for Mobile Communication - Liuyan Han; Rongduo Lu; Jiachen Li; Xinyu Chen; Hui Cao; Jia Shen; Dechao Zhang; Han Li (IEEE Access)
Time synchronization networks are vital infrastructures for numerous applications. We introduce an innovative architecture addressing the high-precision requirements of national time networks. This scheme combines DCV (distributed common-view) time transfer in the backbone with TDM-based (time division multiplex-based) PTP in metro networks. It enables flexible designation of time servers as national primaries. All the time servers are interconnected via a centralized data center. Theoretical analysis and extensive experiments validate successful high-precision national synchronization over large-scale transport networks. Notably, we achieved end-to-end accuracy of 36 ns across 2150 km spanning 3 provinces/cities, marking a milestone. This solution paves the way for future networks and applications requiring ultra-high time synchronization precision.